2009
DOI: 10.1073/pnas.0902639106
|View full text |Cite
|
Sign up to set email alerts
|

Defining the role of syndecan-4 in mechanotransduction using surface-modification approaches

Abstract: The ability of cells to respond to external mechanical stimulation is a complex and robust process involving a diversity of molecular interactions. Although mechanotransduction has been heavily studied, many questions remain regarding the link between physical stimulation and biochemical response. Of significant interest has been the contribution of the transmembrane proteins involved, and integrins in particular, because of their connectivity to both the extracellular matrix and the cytoskeleton. Here, we dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
88
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 116 publications
(89 citation statements)
references
References 45 publications
1
88
0
Order By: Relevance
“…We and others have also demonstrated that S4 plays a critical role in the control of cell polarity, by controlling Rho GTPase activity (9)(10)(11), as well as in planar cell polarity (12). S4 has also been recently identified as a putative mechanosensor (13).…”
mentioning
confidence: 73%
“…We and others have also demonstrated that S4 plays a critical role in the control of cell polarity, by controlling Rho GTPase activity (9)(10)(11), as well as in planar cell polarity (12). S4 has also been recently identified as a putative mechanosensor (13).…”
mentioning
confidence: 73%
“…In addition to flow, syndecan 4 also has the ability to respond to directly applied mechanical tension (Bellin et al, 2009). However, the molecular mechanism underlying the syndecan 4-dependent shear stress response is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Its heparan sulfate (HS) chains and core protein could control the stability, movement and reception of diffusible heparin-binding growth factors (1). In addition, it can form physical connections between the extracellular matrix (ECM) and intracellular signaling to affect the growth and differentiation of a number of tissues and organs (2,3). SDC4 is highly complex by virtue of its external side chains, and thus interacts with a variety of ligands, such as vascular endothelial growth factors (VEGFs), platelet-derived growth factors (PDGFs) and fibroblast growth factors (FGFs) (4).…”
Section: Introductionmentioning
confidence: 99%